(untitled) (Journal of Psychiatrists’ Association of Nepal, 2019)
Introduction: Methadone maintenance treatment program is one of the accepted form of treatment modalities for opioid dependence individuals in Nepal. Retention in the treatment represents the assessment of the effectiveness of the treatment program. The aim of this study was to find out the factors associated with the retention of clients in the Methadone maintenance clinics in the Kathmandu Valley. Material and Method: A total of 84 clients were recruited from the 5 different methadone clinics of Kathmandu valley. A prospective follow-up design was used. The patients were followed up at the end of 6 months and retention rate was calculated. The patient was considered ‘drop out “if the patient did not take methadone for 7 consecutive days. Group differences between ‘dropout’ and non-dropout (retained) clients on MMT program were tested using t-test and Chi-square test for continuous variables and categorical variables respectively. Results: At the end of 6 months 63 patients still remained in the MMT program, so the retention rate was found to be 75% in the study. The factors associated with the retention included higher dosage of methadone (p<0.001), history of multiple substance intake (p=0.004) and previous treatment history of the drug related problems (p=0.015). Conclusion: Opioid dependent individuals may stick to the MMT program for longer durtion if they are offered with higher dosage of Methadone and special attention should be given to the patients with history of poly substance abuse and prior treatment history to prevent their relapse.